Pedagogical Management as a Special Type of Management Activity - Murodov Nodirbek Oybek o‘g‘li (Genius Journals, 2022)
In the article, the authors turn to understanding the issues of the pedagogical process from the position of management. The origin of the term "management" is indicated. The goals of management as a specific type of management activity are determined. The authors of the article note the factors of the emergence of the term "management" in domestic pedagogical science and practice. Pedagogical management is considered by the authors as a special branch of management with its own specifics and patterns. Definitions of pedagogical management are given by various authors.
Keywords: Management; education management; managerial activity; pedagogical management